Peningkatan Taraf Hidup Masyarakat UMKM Rambak Melalui Sosialisasi Pemanfaatan Kredit Usaha Rakyat di Desa Bangsal Kabupaten Mojokerto - Agung Wijaya (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The goal of the socialization program for People's Business Credit (KUR) use in Bangsal Village, Mojokerto Regency, is to enhance the community's knowledge, perspectives, and practices about KUR for MSMEs. Prior to and during the socializing activity, questionnaires and in-depth interviews were used to gather data for this qualitative research. The study's findings demonstrated a decline in the usage of KUR for non-productive consumption and an increase in community awareness of the advantages and prerequisites for using KUR. The community is positively encouraged to use KUR for their business requirements as a result of this socialization program. Increased stakeholder participation, improved instructional materials, wider outreach, and ongoing monitoring and evaluation are all required to improve the efficacy of KUR socialization. In order to promote regional economic growth and enhance community welfare overall, it is anticipated that the findings of this research would significantly increase access to and advantages of KUR.